Analisis Keputusan Pembelian Konsumen saat Live Shopping pada Platform TikTok Produk Fashion - Erwin Permana; Muhammad Rafi Putra Prasetia; Muhammad Rafif Falah; Agustinus Miranda Wijaya (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The strengthening of the digital ecosystem has changed the way people make purchasing decisions. This study aims to analyze consumer purchasing decisions in live shopping on the TikTok platform for fashion products. The study was conducted using a descriptive qualitative approach. The research data was sourced from digital searches and observations. The results of the study indicate that consumer purchasing decisions in live shopping on TikTok are influenced by several key factors, namely seller credibility, promotional systems, interactivity, transaction ease, and social influence. These factors interact with one another and shape a satisfying shopping experience for consumers, thereby encouraging them to make purchases. By understanding these factors, businesses can design more effective marketing strategies to maximize sales through the TikTok platform.